'One-stop-shop' diagnosis and stage-adapted surgical therapy for small nodules of early stage lung cancer in a hybrid operating room. (1st June 2022) - Caviezel, C; Kostopanagiotou, K; Puippe, G D; Werner, R S; Opitz, I
Abstract: Objective: Emergent lung cancer screening programs increased detection of small pulmonary nodules. Anatomical resection in case of early-stage lung cancer with only one intervention becomes increasingly desirable. Current literature lacks procedure data about both diagnosis and subsequent indicated resection. After starting our hybrid operating room program, we reviewed the efficacy of detection, diagnosis and therapy in one-step. Methods: Undiagnosed pulmonary nodules suspicious of lung cancer, which were not detectable by conventional video-assisted thoracoscopic surgery (VATS) due to localization and size, were scheduled for a hybrid procedure consisting of a cone-beam CT-guided hookwire insertion and C-arm assisted thoracoscopic wedge resection for frozen section. All procedures were analyzed for perioperative outcomes including success rate of image-guided nodule resection and rate of concomitant correct anatomical resection. Results: Between July 2020 and July 2021, 23 patients with 25 nodules underwent image-guided VATS (iVATS) in the hybrid room. Twenty-two nodules were successfully marked by hookwire, three nodules were detected by ultrasound in one case and palpation in two cases. In 16 patients (70%) wedge resection with frozen section showed malignancy. Five patients with previous history of operated lung cancer received only a diagnostic wedge, as frozen section could not differentiate between primary or metastatic lung cancer. Eleven patients (48%) had early-stage primary lung cancer (8 adenocarcinoma, one typical carcinoid, one small-cell lung cancer and one squamous-cell lung cancer). Ten of them (91%) received a synchronous completion anatomical resection (seven lobectomies, three segmentectomies). In one patient, malignancy was only confirmed in final histology. Conclusion: One-stop-shop diagnosis and treatment by iVATS with frozen section and concomitant completion anatomical resection in a hybrid operating room for otherwise non-well approachable early stage lung cancer is patient-convenient for the increasingly detected small pulmonary nodules.